Reading with feeling affect theory and the Bible - Black, Fiona C.; Koosed, Jennifer L. (Atlanta Society of Biblical Literature, 2019)
Cover -- Contents -- Abbreviations -- Introduction -- Affect and Animality in 2 Samuel 12 -- Echoes of How -- The Affective Potential of the Lament Psalms of the Individual -- Public Suffering? -- Prophecy and the Problem of Happiness -- The Disgusting Apostle and a Queer Affect -- "Not Grudgingly, nor under Compulsion" -- "Though We May Seem to Have Failed" -- Responses -- Palpable Traumas, Tactile Texts, and the Powerful Reach of Scripture -- The Rage for Method and the Joy of Anachronism -- Contributors -- Ancient Sources Index -- Modern Authors Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Bible-Criticism, interpretation, etc; Aufsatzsammlung